2012
DOI: 10.2478/s11756-012-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the protozoan toxin climacostol and its derivatives

Abstract: Climacostol is a defense toxin produced by the ciliated protozoan Climacostomum virens and belongs to resorcinolic lipids, a group of compounds that shows antimicrobial, antiparasitic, and cytotoxic activities. In this study we investigate the antimicrobial activity of climacostol and its alkyl and alkynyl derivatives against a panel of bacterial and fungal pathogens. Our results show a good and comparable antimicrobial activity of the three compounds, which have resulted effective against Gram-positive bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
(32 reference statements)
1
21
0
1
Order By: Relevance
“…Recent studies performed to evaluate the effects of climacostol on bacteria, fungi, protozoa, human cancer cell lines, and isolated rat mitochondria have suggested that the protozoan toxin exhibits this spectrum of activities, and have indicated some peculiar structural and functional traits of the molecule. Petrelli et al [14] have reported that climacostol can exert a potent antimicrobial activity against a panel of bacterial and fungal pathogens, including Staphylococcus, Streptococcus, Enterococcus, and Candida. Buonanno and Ortenzi [15] demonstrated that the cytotoxic potency of climacostol on free-living freshwater ciliates can be modulated by the substitution of the double bond in the aliphatic chain of the toxin with a single or a triple one.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies performed to evaluate the effects of climacostol on bacteria, fungi, protozoa, human cancer cell lines, and isolated rat mitochondria have suggested that the protozoan toxin exhibits this spectrum of activities, and have indicated some peculiar structural and functional traits of the molecule. Petrelli et al [14] have reported that climacostol can exert a potent antimicrobial activity against a panel of bacterial and fungal pathogens, including Staphylococcus, Streptococcus, Enterococcus, and Candida. Buonanno and Ortenzi [15] demonstrated that the cytotoxic potency of climacostol on free-living freshwater ciliates can be modulated by the substitution of the double bond in the aliphatic chain of the toxin with a single or a triple one.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we were able to stably maintain the in vitro growth of seven species of ciliates: Euplotes aediculatus, Euplotes eurystomus, Paramecium bursaria, Paramecium caudatum, Spirostomum minus, Spirostomum teres and Tetmemena pustulata. The ability to grow these organisms in vitro using cerophyl medium (Sonneborn, 1957) expands the possibilities of future applied studies such as acute trials (ecotoxicology), detection, characterization and isolation of secondary metabolites, characterization of molecules with antimicrobial activity, contributing to neotropical water monitoring programs (Madoni and Romeo, 2006;Petrelli et al, 2012;Mansano et al, 2016). This present study contributes to a better comprehension about the diversity of ciliated protists in limnic ecosystems in Brazil and emphasizes the importance of development Braz.…”
Section: (With 1 Figure)mentioning
confidence: 74%
“…Alkylresorcinols, also known as resorcinolic lipids or 5-alkylresorcinols, possess a 1,3-dihydroxybenzene core with an alkyl or an alkenyl chain at 5-position of the aromatic ring [1].…”
Section: Introductionmentioning
confidence: 99%
“…Adeninealkylresorcinol (1), an unusual alkylresorcinol, is the first case of alkylresorcinol tethered with nucleobase. In addition, the antioxidant effect of 1-3 was evaluated by ORAC method, and they showed potent antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%